Unemployment rate in Malaysia: Does Okun’s Law & Philips curve exist? - Cherylad Jikunan; Siti Hajar Samsu; Beatrice Lim Fui Yee (Universiti Malaysia Sabah, 2021)
Malaysia is on the track of becoming a developed country towards 2020. However, to achieve such target is not easy. Malaysia is expecting to reach the unemployment rate of 2.8% in the year 2020. Hence, the objective of this study is to examine determinants of unemployment rate in Malaysia from the year 1982 to 2017. Secondary data is used and collected from the World Bank’s official website and the Department of Statistics Malaysia. The study employed the Johansen Cointegration test and Vector Error Correction Model (VECM) to identify the long and short-run relationship. Granger Causality test is used to find the causation between the unemployment rate and the variables studied. The result found all variables are cointegrated in long run and short run. Besides, all the variables have no causality with each other except for the LSEC variable (secondary education level). Inflation rate and GDP growth is found to be positively significant to unemployment rate. Thus, Okun’s Law and Philips Curve do not exist in Malaysia case. The inflation rate has been identified as the main determinants of the unemployment rate in Malaysia. The positive relationship it has with unemployment rate indicates in Malaysia case it is known as stagflation situation. Malaysia must formulate the economic policy that enable to lower inflation without exacerbate unemployment rate. In addition, policy makers should take a necessary action towards the issue of job mismatch and job vacancy in the labour market that may lead to exacerbate unemployment rate in Malaysia.